مصطلح أصح شيءٍ في الباب في كتب السنن الأربعة وأثر ذلك في عمل الفقهاء: The Terminology of Asah al-Shay’ fi Hadha al-Bab in Four Canonical Hadith Collections and Its Influence on The Ruling of Jurists - Salman Abed Rabbo Abu Sailik, Abed Rabbo (Maʿālim al-Qurʾān wa al-Sunnah, 2019)
This article deals with a terminology of asah al-shay’ fi hadha al-bab (the most correct thing for this section) as described by hadith scholars of four Sunan collections. The study elaborates the possible meaning of this terminology according to the contextual perspective of how it was established and the effect on regulating process of jurists’ rulings. Hence the purpose of this paper first is to determine the meanings of the terminology then takes a protracted encounter with the impact on the ruling of jurists. This qualitative research which focuses on the inductive, descriptive, critical, and analytical approach are used to the hadiths contained of asah al-shay’ terminology as adopted by the jurists. The finding shows the practice of hadith scholars in using this terminology is not to authenticate the hadiths but contrasting the level of veracity among the hadith transmissions and prioritize them although a hadith would not reach authentic level. And the jurists evidently quote the terminology in a manner agreed upon their principles. Noticeably, they applaud hadith scholars’ viewpoint antecedent to their principles with certain justification if there is any dissimilitude.